Compositores mexicanos y cubanos en Nueva York, c.1880-1920 - Koegel, John (El Colegio de México, A.C., 2006)
Cuban musicians active in New  York in the 1860s through the 1890s such as Ignacio Cervantes, Emilio Agramonte, and Rosalia Chalia assisted in the struggle for Cuban independence from Spain from the vantage point of New York's Cuban émigré community, and they also established  a strong  presence in the city's musical life.  Important Mexican musicians such as Miguel Lerdo  de Tejada and Carlos Curti intermittently visited New York or were long-term residents there. This was especially true during the late- nineteenth century, when the forced political stability during the Porfiriato made possible the extended visits of Mexican musicians and ensembles to North American cities such as New York. The Mexican Revolution also sent Mexican musicians to the United States in search of political freedom as well as economic and artistic opportunities that were temporarily closed to them in Mexico.